2008
DOI: 10.1177/039139880803100306
|View full text |Cite
|
Sign up to set email alerts
|

The Acid-Base Effect of Changing Citrate Solution for Regional Anticoagulation during Continuous Veno-Venous Hemofiltration

Abstract: (Int J Artif Organs 2008; 31: 228-36)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Egi et al found that increasing the citrate dose during RCA-CVVH significantly attenuated magnitude and duration of metabolic acidosis [9]. When administering respectively 11 and 14 mmol/L citrate (ie a SIDa of respectively 33 and 42 mmol/L), they observed an alkalinizing effect depending on the SIDa of the replacement fluid and an acidifying effect due to an increase in unmeasured anions [9, 17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Egi et al found that increasing the citrate dose during RCA-CVVH significantly attenuated magnitude and duration of metabolic acidosis [9]. When administering respectively 11 and 14 mmol/L citrate (ie a SIDa of respectively 33 and 42 mmol/L), they observed an alkalinizing effect depending on the SIDa of the replacement fluid and an acidifying effect due to an increase in unmeasured anions [9, 17].…”
Section: Discussionmentioning
confidence: 99%
“…When administering respectively 11 and 14 mmol/L citrate (ie a SIDa of respectively 33 and 42 mmol/L), they observed an alkalinizing effect depending on the SIDa of the replacement fluid and an acidifying effect due to an increase in unmeasured anions [9, 17]. The highly different citrate flow between groups (1.83 vs. 3.10 mmol/L blood, 22 vs. 28 mmol/h, and 520 vs. 672 mmol/day) might explain the observed alkalinizing effect [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, it is directly linked to the increased SID due to the significant load of sodium from trisodium citrate, during citrate metabolization. Egi et al [8] compared a C14 with a C11 solution (also low concentration or diluted citrate) and found more metabolic alkalosis in the C14 arm. Daily infused citrate was higher in patients receiving C14, which translated into a corresponding additional bicarbonate load that shifted acid-base balance toward metabolic alkalosis.…”
mentioning
confidence: 99%